Beloglavi jastreb Gyps fulvus - Šere, Dare (Acrocephalus, 1998)
6 at corpses of 4 sheep killed a few days earlier by lightning, on 21st to 22nd May 1993 at Vrh Klonic above Tolmin
Keywords: beloglavi jastreb; Griffon Vulture; opazovanje; ornithology; ornitologija; Slovenia; Tolmin; Vrh Klonic